Undergraduate Students’ Perceptions of Electronic and Handwritten Feedback: A Follow-up Study across an Entire Midwestern University Campus - Ni Chang; Bruce Watson; Michelle A. Bakerson; Frank X McGoron (Journal of Teaching and Learning with Technology, 2013)
Some instructors, besides awarding grades, provide comments/feedback on students’ assignments. Views of students on feedback help frame effective and efficient teaching and learning. However, students’ perceptions of feedback, including handwritten and electronic feedback (e-feedback), are under researched. To fill the void, in the academic year 2012 to 2013, all undergraduate students at a Midwestern university were invited to complete a survey for the purposes of exploring their  perceptions of which feedback form they preferred: handwritten or e-feedback and of understanding related rationale behind their preferences related to accessibility, timeliness, legibility, quality and personal. The data were analyzed quantitatively and qualitatively, and show that the majority of the respondents preferred e-feedback. With respect to rationale, more respondents and higher ratings overall were given to e-feedback for timeliness, accessibility, and legibility. Although more respondents overall favored e-feedback the overall ratings were higher in handwritten feedback for its quality and personal. Age and class standing are positively associated with students’ desire for feedback in general and for e-feedback. However, there was a negative association between students’ GPA and feedback in general and e-feedback. Addressed in this article are also limitations, educational implications, and future research suggestions.